Development of a risk score to predict abnormal glycemic status among Thai dental patients - Chanita Tantipoj; Natchalee Srimaneekarn; Sirirak Supa-amornkul; Vitool Lohsoonthorn; Narin Hiransuthikul; Weerapan Khovidhunkit; Siribang-on Piboonniyom Khovidhunkit (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - To construct a risk score using both clinical and intra-oral variables and to determine a risk score to screen individuals according to their risk of hyperglycemia. Design/methodology/approach - A cross-sectional study was carried out among 690 Thai dental patients who visited the Special Clinic, Faculty of Dentistry, Mahidol University and a mobile dental unit of His Majesty the King of Thailandss Dental Service Unit. Participants aged ≥25 years without a previous history of type 2 diabetes mellitus were included in the study. Participants diagnosed with severe anemia and polycythemia were excluded. Questionnaires were used to collect demographic data. Point-of-care HbA1c, body mass index (BMI), blood pressure and periodontal status were analyzed. Findings - A total of 690 participants were included in the study. A risk scoring system including five variables was developed. It exhibited fair discrimination (area under the curve = 0.72, 95%CI 0.68-0.71). The risk score value of 9 was used as the cut-off point for increased risk of abnormal HbA1c. Subjects that had a total risk score of 9 or more had a high probability of having abnormal HbA1c and were identified for referral to physicians for further investigation and diagnosis. Originality/value - A risk score to predict hyperglycemia using a dental parameter was developed for convenient evaluation in dental clinics.